2011
DOI: 10.1016/j.biomaterials.2011.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the brain with PEG–PLGA nanoparticles modified with phage-displayed peptides

Abstract: The relative impermeability of the blood-brain barrier (BBB) results from tight junctions and efflux transport systems limits drug delivery to the central nervous system (CNS), and thus severely restricts the therapy of many central nervous system diseases. In order to enhance the brain-specific drug delivery, we employed a 12-mer phage display peptide library to isolate peptides that could target the drug delivery system to the brain. A 12-amino-acid-peptide (denoted as Pep TGN) which was displayed by bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
165
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 259 publications
(172 citation statements)
references
References 28 publications
6
165
0
1
Order By: Relevance
“…Different cells including MDCK cells [17,20,24,29] , BCECs [19,26,33,40] , bEnd.3 cells [28,39] , and glioma cells [20,34,37,41] were used as in vitro cell models treated at doses ranging from 10 to 15,000 μ g/ml. Small size, positively charged and less hydrophilic NPs were associated with enhanced cellular uptake [17] .…”
Section: Uptake Efficiencymentioning
confidence: 99%
See 4 more Smart Citations
“…Different cells including MDCK cells [17,20,24,29] , BCECs [19,26,33,40] , bEnd.3 cells [28,39] , and glioma cells [20,34,37,41] were used as in vitro cell models treated at doses ranging from 10 to 15,000 μ g/ml. Small size, positively charged and less hydrophilic NPs were associated with enhanced cellular uptake [17] .…”
Section: Uptake Efficiencymentioning
confidence: 99%
“…A number of in vitro experiments have demonstrated that surface functionalized NPs enhanced the therapeutic efficacy of antitumor drugs against the glioma cells such as RG2 and C6 glioma cells when compared with that of free drugs in solution and unmodified NPs with entrapped drugs [17,20,28,32,37,41] . Besides cell viability, IC 50 , the concentration of the drug required to kill 50 % of the incubated cells over a fixed time period, was employed to quantify and evaluate the cytotoxicity of NPs loaded with chemotherapeutic drugs, and their therapeutic efficiency.…”
Section: Therapeutic Efficacymentioning
confidence: 99%
See 3 more Smart Citations